Ammonia Synthesis Under Ambient Conditions: Selective Electroreduction of Dinitrogen to Ammonia on Black Phosphorus Nanosheets. Issue 9 (14th January 2019) - Zhang, Lili; Ding, Liang‐Xin; Chen, Gao‐Feng; Yang, Xianfeng; Wang, Haihui
Abstract: Constructing efficient catalysts for the N2 reduction reaction (NRR) is a major challenge for artificial nitrogen fixation under ambient conditions. Herein, inspired by the principle of "like dissolves like", it is demonstrated that a member of the nitrogen family, well‐exfoliated few‐layer black phosphorus nanosheets (FL‐BP NSs), can be used as an efficient nonmetallic catalyst for electrochemical nitrogen reduction. The catalyst can achieve a high ammonia yield of 31.37 μg h −1 mg −1 cat. under ambient conditions. Density functional theory calculations reveal that the active orbital and electrons of zigzag and diff‐zigzag type edges of FL‐BP NSs enable selective electrocatalysis of N2 to NH3 via an alternating hydrogenation pathway. This work proves the feasibility of using a nonmetallic simple substance as a nitrogen‐fixing catalyst and thus opening a new avenue towards the development of more efficient metal‐free catalysts. Abstract : Well‐exfoliated few‐layer black phosphorus nanosheets (FL‐BP NSs) were developed as an efficient nonmetallic catalyst for electrochemical nitrogen reduction. The catalyst can achieve a high ammonia yield of 31.37 μg h −1 mg −1 cat. under ambient conditions. DFT calculations show that the zigzag and diff‐zigzag edges of the FL‐BP NSs are the active centers, which enable selective electroreduction of N2 to NH3 via an alternating hydrogenation pathway.